Review on climate change, microbial resilience, and disease risks in global aquaculture systems - Sivakamavalli Jeyachandran (Comparative Immunology Reports)
Climate change is fundamentally changing the shape of global aquaculture systems in terms of altering temperature regime, salinity, pH, and oxygenation of aquatic environments. These are altering microbial communities, and the latter are important for maintaining the ecosystem and disease regulation balance. This review focuses on the interrelationship between climate-borne stressors, microbial endurance, and the escalating levels of aquatic diseases. It underscores how variations in microbial dynamics may either cushion or inflate outbreaks of pathogens, impacting the health of the fish and the productivity of aquaculture. The study of these complex interactions is essential for devising adaptive strategies that will improve the resilience of the system, facilitate sustainable practices of aquaculture, and minimize the threat from emerging diseases in a warming world.